2014
DOI: 10.1111/jtsa.12110
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrap Sequential Tests to Determine the Order of Integration of Individual Units in A Time Series Panel

Abstract: We propose an approach to investigate the unit root properties of individual units in a time series panel or large multivariate time series, based on testing user‐defined increasing proportions of hypothesized I(0) units sequentially. Asymptotically valid critical values are obtained using the block bootstrap. This sequential approach has an advantage over multiple testing approaches as it can exploit the (cross‐sectional) dimension of the system, which the multiple testing approaches cannot do effectively. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 29 publications
0
46
0
Order By: Relevance
“…As Smeekes (2011) shows, the above procedure is asymptotically (as T → ∞) valid in the sense that if q is among the quantiles to be tested, then…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…As Smeekes (2011) shows, the above procedure is asymptotically (as T → ∞) valid in the sense that if q is among the quantiles to be tested, then…”
Section: Methodsmentioning
confidence: 96%
“…. , c 4 are set as in Smeekes (2011) to the negative inverse of the α-level critical values for each test statistic, which are obtained in a preliminary bootstrap step.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BST described above is asymptotically valid (see Smeekes, ). More specifically, as T → ∞, it can be shown that: (i) FWER ≥ α ; and (ii) if γ i < 0, then the null hypothesis that the LOP does not hold will be rejected with probability tending to 1.…”
Section: Econometric Methodologymentioning
confidence: 99%
“…Other approaches have been recently proposed in the literature to determine the stationarity of individual time series in panels (see, e.g., Ng, 2008;Hanck, 2009;Moon and Perron, 2012;Smeekes, 2015); however, these procedures cannot be strictly labelled as spsm (in the sense used by Chortareas and Kapetanios, 2009) and cannot be analyzed using our simulation method, specifically tailored on Chortareas and Kapetanios (2009).…”
Section: Go Tomentioning
confidence: 99%